(untitled) (African Journal of Biomedical Research, 2023)
Palatal perforation can be due to congenital or acquired causes. Aetiologies of palatal perforations include developmental disorders, infections, immune suppressed state, malignancy, and drugs abuse among others. Patients with palatal perforation experience various problems among which are phonation, feeding difficulties and psychological trauma. In this article, we discussed a rare case of palatal perforation due to chronic sinusitis in a 42-year-old HIV positive patient. The perforation was managed with a close hollow bulb palatal obturator, following which there was an improvement in patient’s phonation, feeding and psychological wellbeing. Palatal perforation should be seen as one of the possible complications in an HIV patient with low CD4 count and the defect can be managed by the use of prosthesis.